ARTERIAL WALL RIGIDITY IN PATIENTS WITH CHRONIC HEART FAILURE WITH PRESERVED SYSTOLIC FUNCTION OF THE LEFT VENTRICULAR - Kityan S.A. (Scholar Express Journals, 2022)
In recent years, the number of patients with chronic heart failure with preserved ejection fraction (CHFsEF) of the left ventricle has sharply increased. It was found that the rigidity of the main arteries in patients with CHF-eFV of ischemic genesis is increased. An increase in central aortic pressure and augmentation index was also revealed. It was noted that the severity of CHF depends on the increase in the parameters of central hemodynamics. The relationship between increased rigidity of great vessels and NT-proBNP levels in patients with CHF-eFV was revealed.
Keywords: Chronic Heart Failure; Arterial Stiffness; Central Hemodynamic Parameters; Natriuretic Peptide